IMPLEMENTASI PROGRAM JUMAT AL-MA’UN (JUMUN) SEBAGAI GERAKAN FILANTROPI DI SMA MUHAMMADIYAH 4 SURABAYA - Yhogi Dewangga, Dhigi; Mardayanti; Mardiana, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Jumun (Jumat Al-Maun) program at Muhammadiyah 4 High School in Surabaya, as a form of Muhammadiyah's philanthropic movement through infaq and alms activities to help students in need. This study used a descriptive qualitative approach. The results show that the Jumun program is implemented systematically through stages of socialization, fundraising, management, and distribution to students in need. This program involves the active participation of all school members, especially students through the Muhammadiyah Student Association (IPM). The implementation of the Jumun program serves not only as a social activity but also as a means of character education based on the theological values ​​of Al-Ma'un. The program's impact is seen in increased empathy, social awareness, and the habit of sharing among students. Furthermore, the program strengthens solidarity among students and fosters a culture of philanthropy within the school environment. The Jumun (Jumat Al-Ma'un) program can be categorized as a model for implementing school-based philanthropic education that is effective in shaping students' social and religious character and has the potential to be developed in other educational institutions. Keywords: Philanthropy, Jumat Al-Ma'un, and Muhammadiyah